Ovarian activity reversibility after the use of deslorelin acetate as a short-term contraceptive in domestic queens - Ackermann, C. L. [UNESP]; Volpato, R. [UNESP]; Destro, F. C. [UNESP]; Trevisol, E. [UNESP]; Ruas Sousa, N. [UNESP]; Guaitolini, C. R. F. [UNESP]; Derussi, A. A. P. [UNESP]; Rascado, T. S. [UNESP]; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2012)
The objective was to evaluate ovarian activity reversibility in domestic queens after short-term contraceptive treatment with deslorelin acetate. Ten mature queens were used. In all queens, the estrous cycle was evaluated every 72 h by vaginal cytology (VC) and behavior assessments. When queens had VC characteristic of interestrus or diestrus, one deslorelin acetate implant (4.7 mg) was placed in the subcutaneous tissue of the interscapular region (day of insertion = Day 0). Thereafter, VC was performed every 48 h and on Day 90, implants were removed. At Day 100, estrus and ovulation were induced with 100 IU eCG (im), followed by 100 IU hCG (im), 84 h later (Day 103.5). Queens were ovariohysterectomized on Day 106. Corpora lutea (CL) were counted, oviducts were flushed, and oocytes were identified, isolated and stained to assess viability. In all queens, blood samples for plasma progesterone concentrations were collected once a week, from Days -21 to 106. After deslorelin acetate application, four queens had VC and behavior typical of estrus, and one ovulated. Furthermore, ovulation occurred in three queens that did not have VC or behavior consistent with estrus. After the initial ovarian stimulation, all females had anestrous VC during the deslorelin treatment period. Implants were readily removed. Following implant removal, all females responded to treatments to induce estrus and ovulation. There were (mean +/- SEM) 13.1 +/- 5.5 CL and 8.1 +/- 5.5 oocytes per queen; the oocyte recovery rate was 56.8 +/- 25.4% and all recovered oocytes were viable. We concluded that deslorelin acetate can be used as a reversible short-term contraceptive in domestic cats, because estrus and ovulation were successfully induced following implant removal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Deslorelin acetate; Contraception; Domestic cat; Oocyte recovery